If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -11 = 30 Reorder the terms: -11 + 3x = 30 Solving -11 + 3x = 30 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '11' to each side of the equation. -11 + 11 + 3x = 30 + 11 Combine like terms: -11 + 11 = 0 0 + 3x = 30 + 11 3x = 30 + 11 Combine like terms: 30 + 11 = 41 3x = 41 Divide each side by '3'. x = 13.66666667 Simplifying x = 13.66666667
| x/2+2/3=3/4 | | v=x(25-2x)(12-2x) | | 7p-5(3+p)=7p-15-5p | | -16=4a+2a | | 16.7d+66.7=25d+-.5 | | .666(5)= | | 3.5s-7.3=-7.3+2.6s | | (2x-11)/3=4+x | | x+7/2=7 | | -8x-16=-8(2x-6) | | -16=14a+2a | | 16n+1=80 | | 5-(3-f)-5=6(3-f) | | (5x/2)=3x+5 | | (2x-11)/3=4/3+x | | 22/11x9-3^2 | | 5y=-6(0)-30 | | (x+2)/(x-3)=2 | | v=x(18-2x)(9-2x) | | 4x=-2(2x+4) | | x^2+8x+12y+4=0 | | (7xy)-(3xy)= | | 6m+7m=0 | | x(3x^2-5x-2)=0 | | 8+x=-31 | | 6(v+3)-2v=2(2v+3)-14 | | -3=-1/3h-10 | | 2/3x-12 | | 3-(x-4)=48 | | 18=x+3+2x | | 42/18 | | 15-3k=5(k-5)-3k |